Factors Related to Work Fatigue Among Traffic Police - Willia Novita Eka Rini; Rd. Halim; Ully Sarah (Poltekkes Kemenkes Palu, 2023)
Work fatigue is a significant problem related to occupational health and safety since fatigue is a cause of work accidents which are very dangerous for workers. Data reported by the ILO stated that up to two million workers died every year due to accidents caused by work fatigue. This study aims to determine the factors related to work fatigue among Traffic police. This was a quantitative study with an analytical survey method and a cross-sectional research design. The population in this study involved all Traffic Police in Jambi Police Resort. The study samples were selected using total sampling technique involving 40 people. The results of the study revealed that 80% of respondents experienced moderate level of fatigue and 20% of respondents experienced mild level of fatigue. The results of statistical test showed that there was a relationship between age (p=0.003) and years of service (p=0.014) with the level of work fatigue. Furthermore, there was no relationship between nutritional status, history of disease, and workload with work fatigue. It can be concluded that there was a relationship between age and years of service with the level of work fatigue among traffic police. It is expected that respondents perform muscle stretching within rest hours.